Changes in the cross-country ski base properties resulting from the ski use - Puukilainen, E.; Ohtonen, O.; Lemmettylä, T.; Linnamo, V.; Hemming, B.; Laurila, T.; Tapio, S.; Räsänen, M.; Ritala, M.; Leskelä, M. (Sports Engineering, 2013)
In this work, changes in the cross-country ski base properties resulting from stone grinding, skiing, waxing and re-stone grinding have been investigated. The surface topography, crystallinity, wettability and sliding properties of cross-country ski bases were recorded using a selection of measurement techniques: non-contact chromatic confocal microscopy, contact-type surface roughness analyser and scanning electron microscopy (topography), Raman spectroscopy (crystallinity), contact angle measurement (wettability) and a ski tester (sliding properties). The tested skis were used for 150 km and waxed 35 times. The ski base surface became smoother and the orientation and crystallisation of the base material increased. Wear decreased the hydrophobicity and increased the sliding friction. Even though re-grinding did not restore all of the ski base properties, re-grinding improved the wettability and sliding properties. The results help to optimise stone grinding interval to maintain the performance of the skis.